2008
DOI: 10.1021/jp804153g
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Photoelectron Spectroscopy and ab Initio Study of the Adsorbate System O2/PbTe(001) and the Oxide Layer Growth Kinetics

Abstract: The adsorption of molecular oxygen on PbTe(001) surfaces has been investigated using synchrotron radiation induced photoelectron spectroscopy (BESSY II, Berlin). The behavior of adsorbate system O 2 /PbTe(001) was also modeled in complementary DFT-B3LYP studies using a large-cluster approach. For several possible adsorption structures, the adsorption enthalpies, the changes of the effective charges, and the core-level shifts induced by adsorption were calculated. For the energetically most favorable adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
(35 reference statements)
2
25
0
Order By: Relevance
“…This applies for a film thickness X \ X 1 , where X 1 is the upper limit of thickness for the validity of the CMT about the control of ionic transfer by the electric field in the oxide. This inverse logarithmic law of the thin film growth rate is confirmed by experimental data for oxidation of most metals at low temperatures (less than about 100-200°C) and in the initial oxidation stages at more high temperatures [7][8][9][10][11][12].…”
Section: Introductionsupporting
confidence: 70%
“…This applies for a film thickness X \ X 1 , where X 1 is the upper limit of thickness for the validity of the CMT about the control of ionic transfer by the electric field in the oxide. This inverse logarithmic law of the thin film growth rate is confirmed by experimental data for oxidation of most metals at low temperatures (less than about 100-200°C) and in the initial oxidation stages at more high temperatures [7][8][9][10][11][12].…”
Section: Introductionsupporting
confidence: 70%
“…Core-level shifts were calculated in the initial-state approximation as a variation of the electrostatic potentials at the atomic centers as described in Ref. [25]. 085402-2…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In fact, PbTe nanocrystals are prone to rapid surface oxidation (Chen et al, 1997; Yashina et al, 2008; Yang et al, 2008; Zhang et al, 2008) and the presence of a layer of amorphous oxide of Pb and Te was reported already on the surface of PbTe nanocrystals (Zhu et al, 2009). It seems therefore reasonable that these PbTe nanocrystals were coated with an oxide shell.…”
Section: Resultsmentioning
confidence: 99%